A halophilic Chromohalobacter species from estuarine coastal waters as a detoxifier of manganese, as well as a novel bio-catalyst for synthesis of n-butyl acetate - Pereira, Flory; Kerkar, Savita; Dias, Dominic Savio; Gobre, Vivekanand V. (Frontiers in Microbiology, 2023)
Anthropogenic pollution due to ferro-manganese ore transport by barges through the Mandovi estuary in Goa, India is a major environmental concern. In this study a manganese (Mn) tolerant, moderately halophilic Chromohalobacter sp. belonging to the family Halomonadaceae was isolated from the sediments of a solar saltern adjacent to this Mandovi estuary. Using techniques of Atomic absorption spectroscopy, Scanning electron microscopy-Energy dispersive X-ray spectroscopy, Fourier-transform infrared spectroscopy and Atomic Force Microscopy, the Chromohalobacter sp. was explored for its ability to tolerate and immobilize Mn in amended and unamended media with 20% natural salt concentration (w/v). In aqueous media supplemented with 0.1 mM Mn, the Chromohalobacter sp. was capable of sequestering up to 76% Mn with an average immobilization rate of 8 mg Mn /g /day. Growth rate kinetic analysis using Gompertz mathematical functions was found to model the experimental data well. The model inferred that the maximum growth rate of Chromohalobacter sp. was at 10% natural salt concentration (w/v). The Chromohalobacter sp. was further found to be multimetal tolerant showing high tolerance to Iron (Fe), Nickel (Ni) and Cobalt (Co), (each at 4 mM), and tolerated Manganese (Mn) up to 6 mM. Morphologically, the Chromohalobacter sp. was a non-spore forming, Gram negative motile rod (0.726 μ× 1.33 μ). The adaptative mechanism of Chromohalobacter sp. to elevated Mn concentrations (1 mM) resulted in the reduction of its cell size to 0.339 μ× 0.997 μ and the synthesis of an extracellular slime, immobilizing Mn from the liquid phase forming Manganese oxide, as confirmed by Scanning Electron Microscopy. The expression of Mnx genes for manganese oxidation further substantiated the finding. This bacterial synthesized manganese oxide also displayed catalytic activity (∼50% conversion) for the esterification of butan-1-ol with CH3COOH to yield n-butyl acetate. This Chromohalobacter sp. being indigenous to marine salterns, has adapted to high concentrations of heavy metals and high salinities and can withstand this extremely stressed environment, and thus holds a tremendous potential as an environmentally friendly “green bioremediator” of Mn from euryhaline environments. The study also adds to the limited knowledge about metal-microbe interactions in extreme environments. Further, since Chromohalobacter sp. exhibits commendable catalytic activity for the synthesis of n-butyl acetate, it would have several potential industrial applications.